1990
DOI: 10.1177/107110079001000604
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nonweight-Bearing and Weight-Bearing Radiographs of the Foot

Abstract: This study compares the standardized measurements of the foot in nonweight-bearing and weight-bearing radiographs. Both normal and hallux valgus patients were studied. The results show that some changes thought to occur with weight-bearing cannot be consistently demonstrated. Obtaining both weight-bearing and nonweight-bearing views may not be routinely indicated in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 7 publications
0
30
0
2
Order By: Relevance
“…Alignment of the foot and ankle under weightbearing conditions is different from that in nonweightbearing conditions. 2,13 There is controversy regarding the significance of this difference, 29 but clinical disorders of the foot and ankle frequently occur with weightbearing. Several studies have reported the importance of evaluation under weightbearing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Alignment of the foot and ankle under weightbearing conditions is different from that in nonweightbearing conditions. 2,13 There is controversy regarding the significance of this difference, 29 but clinical disorders of the foot and ankle frequently occur with weightbearing. Several studies have reported the importance of evaluation under weightbearing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Alignment of the foot and ankle differs depending upon whether one is nonweight bearing or statically bearing weight [16]. As body mass increases, greater stress is placed on the ligamentous and muscular structures of the foot during weight bearing actions [9].…”
Section: Development Of the Footmentioning
confidence: 99%
“…Therefore, planning of the operation is performed in terms of the obliquity of the bone cut, the extent of the medial-lateral or dorsal-plantar dislocation of the metatarsal head and the correction of the DMAA [22][23][24].…”
Section: Preoperative Planningmentioning
confidence: 99%